Cadaveric White Matter Dissection Study of the Telencephalic Flexure: Surgical Implications - González-López, Pablo; Cossu, Giulia; Thomas, Cynthia M.; Marston, Jeffery S.; Gómez, Cristina; Pralong, Etienne; Messerer, Mahmoud; Daniel, Roy T. (Frontiers in Neurology, 2022)
Neurosurgery has traditionally been overtly focused on the study of anatomy and functions of cortical areas with microsurgical techniques aimed at preserving eloquent cortices. In the last two decades, there has been ever increasing data emerging from advances in neuroimaging (principally diffusion tensor imaging) and clinical studies (principally from awake surgeries) that point to the important contribution of white matter tracts (WMT) that influence neurological function as part of a brain network. Major scientific consortiums worldwide, currently working on this human brain connectome, are providing evidence that is dramatically altering the manner in which we view neurosurgical procedures. The development of the telencephalic flexure, a major landmark during the human embryogenesis of the central nervous system (CNS), severely affects the cortical/subcortical anatomy in and around the sylvian fissure and thus the different interacting brain networks. Indeed, the telencephalic flexure modifies the anatomy of the human brain with the more posterior areas becoming ventral and lateral and associative fibers connecting the anterior areas with the previous posterior ones follow the flexure, thus becoming semicircular. In these areas the projection, association and commissural fibers intermingle with some WMT remaining curved and others longitudinal. Essentially the ultimate shape and location of these tracts are determined by the development of the telencephalic flexure. We have in this study performed a stepwise (medial to lateral and lateral to medial) cadaveric dissections with a view to describing this intricate anatomy. To better understand the 3D orientation of the WMT of the region we have correlated the cadaveric data with the anatomy of the flexure during human neuro-embryogenesis in addition to cross species comparisons of the flexure. The precise definition of the connectome of the telencephalic flexure is primordial during glioma surgery and for disconnective epilepsy surgery in this region.